Social communication - Fiedler, Klaus, 1951- (Frontiers of social psychology., 2007)
This volume is devoted to the fascinating topic of social communication - fascinating because communication is ubiquitous, in that one cannot not communicate. And yet, the art of effective communication can be extremely demanding and elusive, because a tricky trade-off problem has to be solved. For communication to be successful, it must be at once informative - somehow indicating an intended direction of thought or action - as well as subtle - somehow concealing intentions and instrumental goals. Failure to meet the former criterion renders communication uncontrolled and haphazard.